Constitutional jurisprudence:A research in the fields of genesis - bahman zarei; seyed sadrodin moosavi (رهیافتهای سیاسی و بین المللی)
The Constitutional Revolution in Iran is one of the most important events in Iran's contemporary history, which has had significant impacts on Iran's political and social contours and has resulted in important objectives and mental changes. In this revolution, the elites, including intellectuals and scholars, played a decisive role. Among the religious elites, a range of scholars with a positive and interactionist approach to the modern world, religiously justified the new political concepts that formed the foundations of the constitutional political system by taking advantage of the existing capacities in Shia political jurisprudence. They produced such a system of thought that can be referred to as constitutional jurisprudence or jurisprudence of democracy. By using Skinner's contextual hermeneutic method, while rereading the obvious and hidden aspects and layers of this intellectual system, the present research seeks to answer the following question: What were the practical and ideological contexts in which constitutional jurisprudence was born? The findings of the research show that its ideological background was shaped by religious texts, on the one hand, and, new political concepts, on the other hand. Regarding the practical contexts of this intellectual system, the tyranny of the Qajar rulers and the constitutional revolution can be mentioned as two important factors.